IMPLEMENTASI STANDAR PENGELOLAAN PENDIDIKAN DALAM PENINGKATAN MUTU PENDIDIKAN DI SDN 80 KURI LOMPO KECAMATAN. MARUSU KABUPATEN MAROS - Indrawati .; Muhammad Fahreza W; Muh Yunus (STKIP Pembangunan Indonesia Makassar, 2022)
The aims of this study are: (1) To explain how school planning at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros for improving the quality of schools at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros , (2) To explain how the implementation of the school program at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros for improving the quality of schools at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros , (3) To explain how the leadership of the principal at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros for improving the quality of schools at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros and (4) To explain how the implementation of school supervision at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros for improving the quality of schools at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros . This research is a qualitative research with a narrative approach and takes place at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros. The subjects in this study were residents of SDN 80 Kuri Lompo Kec. Marusu Kab. Maros (Principal, Deputy Head, Head of Administration and Administrative Officer). Data collection techniques used are observation, interviews and documentation as well as techniques to check the validity of the data, researchers use triangulation. The results of the study show that the implementation of education management standards in improving school quality at SDN 80 Kuri Lompo, Kec. Marusu Kab. Maros is by (1) Planning the education program at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros has been carried out by referring to education management standards in an effort to improve quality. Program planning at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros stands out more than the other standard points. (2) Implementation of work programs at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros has referred to the RKS and quality improvement. However, there are still many work programs that have not been realized, such as extracurricular activities, improvement of school facilities and infrastructure, due to very few school funding constraints. Therefore, priority work programs are more important. (3) The principal has carried out supervisory activities in improving the quality of the school. This activity is carried out every day. However, it is not in accordance with education management standards. (4) Principal leadership at SDN 80 Kuri Lompo Kec. Marusu Kab. Maros has been carried out with reference to education management standards in improving school quality.Keywords: School Quality Improvement, Education Management Standards